Stargardt patient experiences in the first gene-based clinical trial for an inherited retinal condition in South Africa - Backer, Monique (Department of Pathology, 2025)
Stargardt disease is a genetic condition that causes progressive central vision loss, typically beginning in late childhood or early adulthood. This vision loss is due to a build-up of lipofuscin in the macula, a part of the retina responsible for sharp central vision. Stargardt disease follows an autosomal recessive inheritance pattern and is currently incurable. This study aimed to explore the expectations and experiences of individuals with Stargardt disease who participated in the first gene-based clinical trial for an inherited retinal disorder in South Africa — the SeaSTAR trial. Eighteen individuals completed the trial, and four participants were recruited for in-depth, semi-structured interviews through Retina South Africa and the Pretoria Eye Institute (the trial host site). A qualitative study, based on interpretive phenomenological analysis, was performed utilising thematic analysis. A qualitative, interpretive phenomenological approach was used, allowing rich, first-person accounts to be thematically analysed. Incorporating participants' voices is clinical trial design is essential for improving communication, fostering trust, and making clinical trials more ethically sound and contextually relevant. Despite the growing use of gene therapy globally, little research has been conducted on patient experiences within the African context — a gap this study begins to address. By understanding how participants from diverse environments experience clinical trials, particularly in underrepresented settings, we can better shape future research frameworks to be inclusive, accessible, and responsive to real-world needs. This study found that participants experienced ups and downs throughout the course of the trial in regard to diagnosis, trial introduction, decision making and navigating the trial outcome. Key motivations for participating in the trial were based on hope for closure, finding a cure for future generations, and contributing to the retinal disorders community. Despite unmet therapeutic expectations, participants still valued their involvement and spoke highly of the trial experience. Patient expectations and experiences are essential factors in the design and success of clinical trials. This aspect remains particularly under-researched in the African context due to limited access to clinical trials on the continent. The findings of this study provided insight into physician-research participant interactions and highlighted the intersection of patients with medical advances in genomic medicine and genetic counselling. Furthermore, participants offered recommendations for future clinical trials and valuable insights for ongoing research.